Alcatena's Malón: national identity and cultural work in the American comics industry - Gandolfo, Amadeo (2018)
We aim to analyze a portion of Argentine cartoonist Enrique Alcatena's career. Alcatena has been working since the early 1980s. Known for his baroque style, his intricately drawn fantastic worlds, his love of superheroes and fantasy, and his collaborations with Eduardo Mazzittelli on scripts, Alcatena's career is an example of transnationalism. He has published extensively in Italy (where most of his collaborations with Mazzittelli first appeared) and he also worked for a brief stint on DC and Marvel Comics during the nineties. In this paper we shall consider Alcatena as a transnational artist, with particular focus on his time on DC. There, alongside Chuck Dixon, he created the Super-Malón, a group of superpowered individuals from Argentina. This group, based on a previously existing character from the 1950s called El Gaucho was an attempt on the part of DC Comics to expand its universe to incorporate characters from countries other than the United States. We?ll briefly reconstruct Alcatena's career both in Argentina and in Italy as a way to discuss how his art functions in different national contexts and to analyze how his style and themes change according to the publishing context. But the main focus shall reside in his work for DC: What stereotypes does the Super-Malón embody? What ideas about Argentina does it transpose? How does it relate to other nationalist super-heroes? How does this group insert itself into the DC Universe? How does it relate to the recovery of El Gaucho by Grant Morrison for Batman, Inc.? The objective is to try and invert the usual focus: instead of seeing the influence of the American comics industry in Argentina, and of considering their relationship as one-way, we will attempt to show the possibilities and limitations faced by an Argentinian artist working for American comics, and whether or not his contributions to a shared universe can be lasting.